A hospital-based study of socioeconomic status and clinical spectrum of rheumatic heart disease patients of Assam, North-East India. (August 2018) - Baro, Lokajeet; Sharma, Neha; Toor, Devinder; Chaliha, Mriganka S; Kusre, Giriraj; Baruah, Sreemanta M; Das, Sangeeta
Objective: The aim of this study was to assess the impact of socioeconomic factors in increased prevalence of rheumatic heart disease and its clinical spectrum in Assam, North-East India. Method: A case–control questionnaire-based study of 100 echocardiography confirmed rheumatic heart disease cases with age- and sex-matched healthy controls from Assam medical college and hospital in Dibrugarh, Assam was conducted. Results: There was a trend toward increased risk of rheumatic heart disease and its clinical spectrum with respect to low socioeconomic status. Three parameters were found to be statistically significant in posing increased risk towards rheumatic heart disease: rural dwelling location ( p < 0.0001, odds ratio (OR) 4.1, 95% confidence interval (CI = 2.29−7.45), low monthly income ( p < 0.001, OR=9.5, 95% CI = 4.99−18.1) and education status ( p < 0.05, OR=9.5, 95% CI = 1.866). Out of the severe cases of mitral stenosis, mitral regurgitation and aortic regurgitation, 69.6%, 58.3% and 34% patients were of low socioeconomic status. Conclusion: Socioeconomic factors can be of significant importance in increased prevalence of rheumatic heart disease and might also influence the clinical spectrum of the disease. Increased awareness and up-gradation of socioeconomic status might ameliorate the prevalence of rheumatic heart disease.